Numerical Investigation of Fuel Cooling in Sudden Expansion Structures of Scramjet Engines - Qingjun Wang; Minglei Hu; Zongjie Quan; Yu Chen (Aerospace, 2025)
Local overheating in cavities seriously threatens the safe operation of scramjet engines. To investigate the formation mechanism and control methods of local overheating, this paper conducts numerical simulations on the cooling process of cavity sudden expansion (S-E) structures. A three-dimensional numerical model coupled with pyrolysis reactions is established and validated through experiments. The effects of thermal pyrolysis reactions and cooling channel parameters on flow distribution are analyzed, and comparative studies with different channel parameters are performed. The results show that S-E structures are prone to uneven fuel flow distribution, leading to local over-temperature phenomena, and thermal pyrolysis reactions will aggravate this phenomenon to a certain extent. Increasing the aspect ratio of the channel can enhance the pressure drop at the inlet of the S-E structure and improve the uniformity of flow distribution. When the aspect ratio increases from one to eight, the mass flow distribution deviation ϕm decreases from 0.954 to 0.181. More uniform flow distribution under a larger aspect ratio avoids local over-temperature in the S-E structure, and reduces the coking risk caused by local excessive pyrolysis. This work reveals the fundamental characteristics of cooling heat transfer in the S-E structure of Scramjet engines and can provide recommendations for the design of cooling channels.